The Placement and Role of Pardon in the Function of Crime Suppression - Jovašević, Dragan; Stevanović, Zoran (Zbornik Instituta za kriminološka i sociološka istraživanja, 2008)
In this paper, the authors analyse the concept, characteristics and content of the institution of oblivion, the procedure of giving oblivion, as well as its role in the function of crime suppression. The oblivion is, besides amnesty, an act of mercy that represents grounds for the extinction of criminal sanctions. It is strictly regulated by the clauses of the Criminal legislation, which is based on the clauses of the Constitution of the Republic of Serbia from 2006. In that way, the concept, content, scope, legal effects and importance of the oblivion institution in the Criminal Law of the Republic of Serbia are regulated on a unique basis. By means of this, total guarantees of equal criminal-law treatment of all criminal perpetrators in front of the court and law, and more generally, in this way, legal security and rule of law are raised to a qualitatively higher level, also the realisation of the principles of the legal state is completely ensured. According to the act 110. CL. R. of Serbia, oblivion is a separate act in the form of a decree (decision or act) passed by the President of the Republic. There are three major characteristics of oblivion: a) it is a separate act of the highest organ of state authority – the sovereign (head of state), b) it addresses certain person; c) the content of oblivion is consisted of: release of criminal prosecution, complete or partial release of penalty execution, substitution of passed penalty with milder penalty or parole, giving rehabilitation, cancellation or giving a shorter time of duration of all or certain legal consequences of conviction or cancellation or giving a shorter time of duration of certain security measures: banning of professional activity and duties, banning of driving of motor vehicle and exile of foreigners from country. On the basis of the formerly presented characteristics of oblivion, it can be concluded that it has its role in the correction of legally prescribed penalties and influences on the politics of crime suppression in a certain time period, and in an indirect way, it corrects and controls the work of organs of criminal jurisdiction.